A New Naqli Aqli Indexing Content (Naqli-IC) Psycho-spiritual Neurofeedback (NFB)Training for Recovering Addicts - Asma Abdul Rahman; Maryam Abdul Rahman; Mizan Adiliah Ahmad Ibrahim; Ahmad Abdul Rahman; Mohd Fadhil Md Din (International Journal of Scientific Research and Management, 2024)
Non-Indexed Publication